Rekontruksi Perhitungan Harga Pokok Produksi pada UMKM Eraclassic - B. Bariro; Aisa Tri Agustini (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
The objective of this research is to reconstruct manufacturing cost of bag in UMKM Eraclassic located in Gresik Regency, using job order costing method. Data in this research are collected through observation, interviews, and documentaries. Descriptive qualitative and quantitative method will be used to analyze those data. The results shows that there is a differences between the calculation of manufacturing cost by UMKM Eraclassic and calculation using job order costing method. The result of reconstruction calculation shows that sling bag, fungky bag and duffel bag manufacture cost are Rp 22.680, Rp 30.189, and Rp 41.707 per unit. This results shows that the gross profit accepted by UMKM Eraclassic are Rp 1.972 per dozen, which is too low. Based on those result, UMKM Eraclassic needs to take the manufacturing overhead cost elements, the cost of depreciation of buildings and vehicles and equipment manufacturer into accounts. In addition, based on the existing fee policy on UMKM Eraclasic, direct labor cost and utility cost will be charged to products. Based on job order costing method, direct labor cost should be charged based on the actual cost of the case, while utility expense which is the manufacturing overhead costs will be charged by the rate determined upfront based on basic imposition. Keywords: Manufacturing Cost, Job Order Costing, Cost of Production, Gross Profit